Improved teacher understanding of classroom action research at SMP Negeri 1 Bungoro, Pangkep Regency: Peningkatan Pemahaman guru tentang Penelitian tindakan kelas di SMP Negeri 1 Bungoro Kabupaten Pangkep - Yusniar Rasjid; Muqtakdir Nurfalaq; Moh. Mulyadi Prasetyo; Kamriana (Yayasan Ahmar Cendekia Indonesia, 2020)
Social Service in SMP Negeri 1 Bungoro, located in Pangkep Regency, South Sulawesi. The problem of partners is that teachers still have difficulty planning and implementing Classroom Action Research. An alternative solution to the problem is to provide Classroom Action Research Training to the teachers of SMP Negeri 1 Bungoro, Pangkep Regency. The output target to be achieved is the skill of the teachers of SMP Negeri 1 Bungoro, Pangkep Regency in compiling a Classroom Action Research proposal so that it can improve the quality of learning. The method to be carried out is the presentation of material on classroom action research in PowerPoint displayed on the LCD. From the results of the activities that have been carried out, it is found that there is an increase in the ability of teachers in preparing Classroom Action Research Proposals